Deletion of Salmonella enterica serovar Typhi tolC reduces bacterial adhesion and invasion toward host cells - Hussain, Ashraf; Ong, Eugene Boon Beng; Balaram, Prabha; Ismail, Asma; Kien, Phua Kia (Frontiers in Microbiology, 2023)
Salmonella enterica serovar Typhi (S. Typhi) is a Gram-negative pathogen that causes typhoid fever in humans. One of the factors that contributes to its virulence is the TolC outer membrane pump, which is involved in effluxing toxic compounds and antibiotics. However, the role of TolC in the invasion of host cells by S. Typhi is not well understood. In this study, we investigated the effect of deleting tolC on the invasion of HT-29 epithelial and THP-1 macrophage cells in vitro. We found that the tolC mutant showed a significant reduction in invasion compared to the wild-type strain. We also observed that the expression of several genes (invF, sipA, sipC, and sipD) encoded by Salmonella pathogenicity island 1 (SPI-1), which are essential for the invasion process, was downregulated in the tolC mutant. These results suggest that TolC modulates the expression of SPI-1 genes and facilitates the invasion of host cells by S. Typhi.